Effects of exogenous sucrose on root nitrogen uptake in apple at sub-low root-zone temperature - Xiaoping Zhao; Hanyu Liu; Lijie Li; Deguo Lyu (Chemical and Biological Technologies in Agriculture)
Abstract Sub-low soil temperature in spring can cause stress to the apple roots, reducing root function and inhibiting nitrogen (N) uptake. Exogenous sucrose can protect plants from low temperature stress, however, the role of sucrose in regulating the N uptake in apple roots at sub-low temperature is unclear. In this study, the physiological, transcriptional, and metabolic mechanisms of apple root N uptake regulation by 1% sucrose under sub-low root-zone temperature (LT) were evaluated. The results showed that LT treatment significantly inhibited N uptake (especially NO3 −-N) and metabolism in roots, decreased photosynthetic and chlorophyll fluorescence in leaves, and inhibited the growth of roots (root activity decreased by 68.85%) and above-ground parts, while exogenous sucrose application significantly alleviated this inhibition. Sucrose application accelerated carbon (C) metabolism and increased sugar, acid, and adenosine triphosphate contents in roots. In addition, exogenous sucrose alleviated the inhibition of N uptake by low temperature, increased the NO3 −-N content, and increased the activities of enzymes related to N metabolism (NR, GS, NADH-GOGAT, GPT, and GOT) in roots. Most of the genes associated with C and N metabolism (MdBMY3, MdSS3, MdPFK6, MdCS2, MdNPF4.4, MdGS and MdGDH1) were upregulated under sucrose treatment, as confirmed by transcriptomic data. Furthermore, the transcriptomic and metabolomic results suggested that sucrose may enhance N uptake by increasing the accumulation of luteolin and sinapyl alcohol in flavonoid metabolism. Collectively, these results provided new insights into the role of sucrose in modulating apple root N uptake under sub-low temperature. Graphical Abstract